The impact of ex-auditors' employment with audit clients on perceptions of auditor independence in Malaysia - Ahmad, Maslina (Elsevier, 2015)
It is a common knowledge that auditors often being offered a position in their clients’ firms. However, following the collapse of Enron in 2001 along with other infamous financial scandals like Global Crossing and Waste Management in the US, the accounting profession has been brought into sharp focus particularly regarding issues that may affect auditor independence. One of the issues is the practice of auditors seeking employment with their audit clients. Therefore, the main objective of this study is to examine whether the practice of ex-auditors’ employment with audit clients affects perceptions of auditor independence from the perspective of financial statement users in Malaysia.